Complication and Management of Diabetic Retinopathy - Vivi Cahyani; Suliati P. Amir; Hanna Aulia Namirah (International Medical Journal Corp. Ltd, 2025)
Background: Diabetic retinopathy (DR) is a common microvascular complication of diabetes mellitus that remains a leading cause of preventable blindness worldwide. Chronic hyperglycemia leads to retinal microangiopathy, resulting in progressive damage that may culminate in serious complications. As DR advances, especially into the proliferative stage (PDR), patients may experience vitreous hemorrhage (VH), diabetic macular edema (DME), or tractional retinal detachment (TRD). Methods: This study is a literature review of ten scientific articles published between 2015 and 2024, focusing on the complications and management of DR. Results: The literature highlights that the primary treatment modalities for DR include panretinal photocoagulation (PRP), intravitreal anti-VEGF injections, and vitrectomy. PRP is commonly used for high-risk PDR, anti-VEGF for DME or active neovascularization, and vitrectomy for advanced cases with VH or TRD. Management decisions are highly dependent on the stage of DR and the presence of complications. Conclusion: The management of DR should be adapted to the severity and type of complication. Early diagnosis and timely intervention are crucial to prevent vision loss.